A review on safety practices for firefighters during photovoltaic (PV) fire - Ramali, Mohd Rashid; Mohd Nizam Ong, Nur Aliah Fatin; Md Said, Mohamad Syazarudin; Mohamed Yusoff, Hamdan; Baharudin, Mohd Rafee; Tharima, Ahmad Faiz; Akashah, Farid Wajdi; Mohd Tohir, Mohd Zahirasri (Springer, 2022)
In recent years, it is evident that there is a surge in photovoltaic (PV) systems installations on buildings. It is concerning that PV system related fire incidents have been reported throughout the years. Like any other electrical power system, PV systems pose fire and electrical hazards when at fault. As a consequence, PV fires compromised the safety of emergency responders. Therefore, the objective of this review is to evaluate the elements of firefighters' safety practices and subsequently collate the best safety practices for local fire rescue and firefighters in the event of PV fires. Out of 264 documents, only 20 publications were identified as ˜closely related and were systematically reviewed to evaluate firefighter safety practices from a scholarly perspective. Only 3 of the 20 publications reviewed, discussed the safety practices during PV fires. Thirteen safety practice key points were extracted from the reviewed documents, with nine critical findings highlighted as the hallmark of safety practices during PV fire for firefighters. The lack of academic journals discussing the fire safety aspects proves that there is a low interest in this field which is in dire need of further study and exploration to adhere with the PV population in ensuring a reliable emergency operation to minimize losses or injuries due to accidents.